Trends in Prevalence of Hypertension and Hypertension Phenotypes Among Chinese Children and Adolescents Over Two Decades (1991–2015) - Ye, Xinxin; Yi, Qian; Shao, Jing; Zhang, Yan; Zha, Mingming; Yang, Qingwen; Xia, Wei; Ye, Zhihong; Song, Peige (Frontiers in Cardiovascular Medicine, 2021)
Background: Hypertension is a leading cause of cardiovascular-related morbidity and mortality. Elevated blood pressure (BP) in children is related to long-term adverse health effects. Until recently, few studies have reported the secular trend and associated factors of hypertension phenotypes in Chinese children and adolescents. Methods: From the China Health and Nutrition Survey (CHNS) 1991–2015, a total of 15,143 records of children aged 7–17 years old were included. Following definitions of hypertension from the Chinese Child Blood Pressure References Collaborative Group, we estimated the prevalence of prehypertension, hypertension, stage 1 hypertension, stage 2 hypertension and its phenotypes (ISH, isolated systolic hypertension; IDH, isolated diastolic hypertension; SDH, combined systolic and diastolic hypertension). General estimation equation was used to analyze the trends in the prevalence of hypertension and hypertension phenotypes, and a multivariable logistic regression was constructed to explore the associated factors. Results: During 1991–2015, increasing trends were revealed in BP and hypertension prevalence (P < 0.001) in Chinese children and adolescents. For ISH, IDH and SDH, the age-standardized prevalence increased dramatically from 0.9 to 2.2%, from 6.2 to 14.1%, and from 1.4 to 2.9%, respectively (all P < 0.001). Adolescents aged 13–17 years (OR = 1.76, 95% CI: 1.56–1.97, P < 0.001), general obesity (OR = 2.69, 95% CI: 2.10-3.44, P < 0.001) and central obesity (OR = 1.49, 95% CI: 1.21–1.83, P < 0.001) were positively associated with hypertension, whereas the South region (OR = 0.65, 95% CI: 0.58–0.73, P < 0.001) was a negative factor. Furthermore, body mass index (BMI) and general obesity were linked to the presence of ISH, IDH and SDH. Age, waist circumference (WC) and central obesity were additionally associated with ISH, and sex, age, urban/rural setting, North/South region, WC and central obesity were additionally associated with IDH. Conclusion: BP levels and prevalence of hypertension and phenotypes increased dramatically in Chinese children and adolescents from 1991 to 2015. Regional discrepancy, demographic features, BMI, WC and overweight/obesity status were associated factors of hypertension among youths.